PENERAPAN KONSEP TIME VALUE OF MONEYDAN KRITIK PELAKSANAAN - Desky, Harjoni (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
The development of Islamic financial theory today has become an important issue, such as debate over the concept of time value of money. This study aims to find out, first, the concept of money in conventional and Islamic financial systems; second, the basic concept of time value of money; and third, the concept of Economic value of time. The research method used in this study is a qualitative method. The results showed that in the conventional financial system, money is considered like a commodity as well as goods and services that can be traded, sold and bought and can be used as objects to speculate, whereas in Islam, money is seen as something that should not be hoarded and should not be wasted or dissipated, money is not seen as a tradable commodity and Islam sees money as a means of exchange and has no value in itself; The concept of time value of money states that the current money utility is higher compared to its utility for the same amount of money in the future; the concept of economic value of time emphasizes that time has economic value rather than money which has time value. Keywords: Time Value of Money; Economic Value of Time; Money; Islam; Conventional Abstrak Perkembangan teori keuangan Islam dewasa ini telah menjadi masalah yang hangat diperbincangkan, seperti perdebatan mengenai konsep time value of money. Penelitian ini bertujuan untuk mengetahui, pertama, konsep tentang uang dalam sistem keuangan konvensional dan Islam; kedua, konsep dasar time value of money; dan ketiga, konsep Economic value of time. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif. Hasil penelitian menunjukkan bahwa dalam sistem keuangan konvensional, uang dianggap seperti komoditas seperti halnya barang dan jasa yang dapat diperdagangkan, dijual serta dibeli dan dapat dijadikan objek untuk berspekulasi, sedangkan dalam Islam, uang dipandang sebagai sesuatu yang tidak boleh ditimbun dan tidak boleh disia-siakan atau dihamburkan, uang tidak dipandang sebagai suatu komoditas yang dapat diperdagangkan dan Islam memandang uang sebagai alat pertukaran dan tidak memiliki nilai dalam dirinya sendiri; Konsep time value of money menyatakan bahwa utilitas uang saat ini lebih tinggi dibandingkan dengan utulitasnya untuk uang dengan jumlah yang sama di waktu yang akan datang; konsep economic value of time menekankan bahwa waktulah yang memiliki nilai ekonomi bukan uang yang memiliki nilai waktu. Kata Kunci:Time Value of Money; Economic Value of Time; Uang; Islam; Konvensional.